A controllable asymmetrical/symmetrical coating strategy for architectural mesoporous organosilica nanostructures. Issue 28 (24th June 2016) - Wang, Xue; He, Yapeng; Liu, Chong; Liu, Yunling; Qiao, Zhen-An; Huo, Qisheng
Abstract : By a controllable asymmetrical/symmetrical coating method, we fabricate different morphological Au&PMO Janus, Au@PMO yolk–shell and Au@PMO/mSiO2 yolk–double shell nanostructures. Abstract : We describe a facile and controllable asymmetrical/symmetrical coating strategy for the preparation of various novel periodic mesoporous organosilica (PMO) nanostructures, including Au&PMO Janus, Au@PMO yolk–shell and Au@PMO/mSiO2 yolk–double shell nanoparticles, by using Au@SiO2 nanoparticles as seeds. During this process, ammonia first functions as a basic catalyst facilitating the hydrolyzation and condensation of the organosilica precursor, and additionally as an etching agent selectively in situ dissolving the SiO2 shells of Au@SiO2 nanoparticles to form these unique nanostructures. All these three types of nanoparticles have high surface areas, large pore volumes and tailorable cavity structures. Both the Au&PMO and Au@PMO nanoparticles exhibit excellent catalytic activity for the decomposition of H2 O2 and the reduction of 4-nitrophenol. Based on these unique structural merits and organic–inorganic hybrid components, the fabricated Janus and hollow PMO nanoparticles show much improved hemocompatibility, which could be further applied in nano-biomedicines without the need for surface modification.